A new methodology for the measurement of the reclaimed asphalt degree of binder activation - Pires, Gustavo Menegusso (2018)
Transportation on highways, mostly on asphalt pavements, is crucial for many countries around the globe. It is also known that the maintenance costs are high, pushing companies and researchers towards seeking new alternatives to improve the utilisation of materials, reduce energy consumption, streamline maintenance operations, among others. Another key factor that stands out is the environmental issues, which are directly affected by the construction and maintenance of highways, such as in the consumption of natural resources and the fuel/energy costs. Thus, it becomes realistic to reuse deteriorated materials by recycling the pavement, since all the material can be used for building a new pavement layer. Numerous studies have been reported concerning methods of using reclaimed asphalt (RA) and the performance of mixtures containing RA. It goes without saying that in the case of high-content RA mixtures, correctly predicting the real amount of RA binder available from a selected RA is crucial to obtain asphalt mixtures which comply with design and performance standards. If the RA binder does not blend with the virgin binder as predicted, pavement performance could be compromised. Thus, this thesis is concerned with the amount of RA binder that is available, or activated, for a new mixture. This property is called the Degree of Binder Activation (DoBA) in this thesis, with the thesis divided into three stages: Assessing the DoBA of the selected RA’s, which is the amount of “old” binder that is re-activated in new mixtures, by proposing a practical method based on the Indirect Tensile Test (ITT). The analysis is performed by comparing results between RA samples and an artificial RA produced in the lab. The method includes the evaluation of the DoBA through the conditioning and manufacturing of RA samples over a range of temperatures, from 70°C to 170°C, and mixing times, from 30 seconds to 180 seconds. Results showed that variations in production temperatures are an important factor when considering 100% RA. The same influence was not found by increasing mixing times. The DoBA index proposed can be used to improve the binder and mixture design and is an easy tool/parameter to be determined. Developing design procedures for the resulting RA binders obtained by mixing old RA binder, new bitumen and an additive, while considering the DoBA. The conventional, rheological and performance-related properties of these binders were evaluated. The optimum additive dosage was defined using the penetration and the softening point tests. The performance-related properties are characterised by means of rutting, fatigue and thermal cracking resistance. Moreover, using the DoBA results, the recycled binders outcomes were used to correlate with the recycled mixtures test results in order to validate the DoBA study. Developing asphalt concrete mixture containing 100% RA and manufacturing mixtures in order to analyse the behaviour in terms of rutting, resistance to fatigue, stiffness modulus and moisture sensitivity. Considering the binder design, four RA mixtures were produced, assuming 100%, 75%, 50% and 15%DoBA. Part of the RA binder was assumed to be black rock (for DoBA% less than 100%) and was compensated in the mixtures by adding virgin binder. Relations are identified and established between binders and mixtures using the tests results to verify the DoBA study. The final mechanical tests proved that they can be well correlated with the designed binders. It was found that the bitumen disregarded during the DoBA design is still potentially active in the mixtures. However, the DoBA methodology can still be considered as a useful tool providing good correlation between binders and mixtures and becoming quite promising to transform the RA into a material with its own characteristics. In conclusion, is evident that the bitumen disregarded during the DoBA design is still potentially active in the mixtures. It can also be said that other sources of RA materials may act more like a Black rock than the RA under investigation in this research due to its own characteristics, although this could only be proved by undertaking an extense experimental programme.